2009
DOI: 10.1029/2008jc005059
|View full text |Cite
|
Sign up to set email alerts
|

Field characterization of wave‐induced underwater light field fluctuations

Abstract: [1] A field characterization of the amplitude and periods of the underwater light field fluctuations is presented on the basis of field measurements of the downward and upward irradiances at a deep-sea mooring in the Mediterranean Sea (BOUSSOLE site). The optical time series at this site includes multispectral irradiance measurements at two depths and irradiance profiles taken from free-fall radiometers. It is already several years long and is paralleled by a time series of wind and waves. When pooled together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…By means of our model, we have demonstrated that more developed gravity waves -here one can speak of a sea state -primarily affect deeper water layers, but essentially not the upper most 10 m. This statement is confirmed by Gernez and Antoine (2009), who showed that gravity waves have no evident impact on irradiance fluctuations at approximately 4 m depth and that the wave height has relatively little influence on CV and the spectral peak period of fluctuations. Our earlier measuring campaigns suggested that below 5 m depth, light fluctuations can be described more accurately in terms of wave height and period, rather than wind speed, and that between 3 and 25 m water depth waves with H s of 1.5 to 2.5 m provoke the strongest intensity fluctuations (Hieronymi and Macke, 2010).…”
Section: Discussion Of the Simulation Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…By means of our model, we have demonstrated that more developed gravity waves -here one can speak of a sea state -primarily affect deeper water layers, but essentially not the upper most 10 m. This statement is confirmed by Gernez and Antoine (2009), who showed that gravity waves have no evident impact on irradiance fluctuations at approximately 4 m depth and that the wave height has relatively little influence on CV and the spectral peak period of fluctuations. Our earlier measuring campaigns suggested that below 5 m depth, light fluctuations can be described more accurately in terms of wave height and period, rather than wind speed, and that between 3 and 25 m water depth waves with H s of 1.5 to 2.5 m provoke the strongest intensity fluctuations (Hieronymi and Macke, 2010).…”
Section: Discussion Of the Simulation Resultssupporting
confidence: 71%
“…Nikolayev et al, 1972;Dera and Stramski, 1986;Gernez and Antoine, 2009;Weber, 2010;Hieronymi and Macke, 2010;Darecki et al, 2011). There is general agreement that the most favorable conditions for light focusing by waves prevail at moderate winds between 2 and 7 m s −1 .…”
Section: Discussion Of the Simulation Resultsmentioning
confidence: 97%
See 3 more Smart Citations